Reply to discussion by KV.Sharma, D.Raj and M.Bharathi on “Modelling efficiency of fluid viscous dampers positioning for increasing tall buildings' Resilience to earthquakes induced structural vibrations”, Soil Dynamics and Earthquake Engineering 173 (2023) 108108 - Sharma, K.V.; Parmar, V.; Gautam, L.; Choudhary, S.; Gohil, J. (Soil dynamics and earthquake engineering (1984), 2024)
We appreciate criticism of our study, and we want to address each issue they brought up. However, rather than trying a thorough investigation of all facets of Earthquake engineering, our study exclusively focused on the practical application of fluid viscous dampers (FVDs) in a G+20 story building under varied loads. We are quite concerned by claims of the presentation of fake technical content because our research was carried out honestly and rigorously. Any unintentional technical errors will be fixed in subsequent releases with the critic's detailed criticism. In terms of due diligence, our study was subject to a thorough peer review before publication, and we are willing to address any issues that may arise. In order to ensure that our conclusions are consistent with the findings of the study, misconceptions and a lack of conclusive data will be thoroughly addressed. We are dedicated to enhancing the calibre of our research and value constructive criticism.